The linguistic complexity and factual accuracy of written and verbal summaries of expository text by Grade 10 learners with learning disability (ID) - Fourie, Landi (My University, 2020)
This study investigated the influence of modality on the linguistic complexity and factual accuracy of expository text summaries produced by grade 10 learners with learning disability (LD). Eight participants were asked to produce written and verbal summaries in response to reading novel expository texts. Summaries were analysed in terms of linguistic complexity and factual accuracy, as well as editing, self-assessment, and the influence of prior speech-, occupational-, and remedial therapy on current academic functioning. Paired sample t-tests indicated that TTR was the only measure significantly influenced by modality, with a higher TTR in the written modality. Results further indicated that editing and self-assessment were areas of significant difficulty in this population. The main conclusion of the study is that a change in output modality alone is not sufficient to improve the academic performance of learners with LD. Further research into the impact of modality in the LD population is needed.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Medicine: Child Health (Neurodevelopment) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2020